Chimeric antigen receptor (CAR)-engineered T cells redirected against hepatitis C virus (HCV) E2 glycoprotein. Issue 3 (6th February 2015) - Sautto, Giuseppe A; Wisskirchen, Karin; Clementi, Nicola; Castelli, Matteo; Diotti, Roberta A; Graf, Julia; Clementi, Massimo; Burioni, Roberto; Protzer, Ulrike; Mancini, Nicasio
Abstract : Objective: The recent availability of novel antiviral drugs has raised new hope for a more effective treatment of hepatitis C virus (HCV) infection and its severe sequelae. However, in the case of non-responding or relapsing patients, alternative strategies are needed. To this end we have used chimeric antigen receptors (CARs), a very promising approach recently used in several clinical trials to redirect primary human T cells against different tumours. In particular, we designed the first CARs against HCV targeting the HCV/E2 glycoprotein (HCV/E2). Design: Anti-HCV/E2 CARs were composed of single-chain variable fragments (scFvs) obtained from a broadly cross-reactive and cross-neutralising human monoclonal antibody (mAb), e137, fused to the intracellular signalling motif of the costimulatory CD28 molecule and the CD3ζ domain. Activity of CAR-grafted T cells was evaluated in vitro against HCV/E2-transfected cells as well as hepatocytes infected with cell culture-derived HCV (HCVcc). Results: In this proof-of-concept study, retrovirus-transduced human T cells expressing anti-HCV/E2 CARs were endowed with specific antigen recognition accompanied by degranulation and secretion of proinflammatory and antiviral cytokines, such as interferon γ, interleukin 2 and tumour necrosis factor α. Moreover, CAR-grafted T cells were capable of lysing target cells of both hepatic and non-hepatic origin expressing on their surface the HCV/E2 glycoproteins of the most clinically relevant genotypes, including 1a, 1b, 2a, 3a, 4 and 5. Finally, and more importantly, they were capable of lysing HCVcc-infected hepatocytes. Conclusions: Clearance of HCV-infected cells is a major therapeutic goal in chronic HCV infection, and adoptive transfer of anti-HCV/E2 CARs-grafted T cells represents a promising new therapeutic tool.